PENINGKATAN PRESTASI BELAJAR MAHASISWA PADA MATA KOMPUTER PEMROGRAMAN MELALUI PEMANFAATAN RECORDING MACRO - Tiwan, Tiwan (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
ABSTRACT The learning process of computer programming course requires the skills of programming flow arrangement and programming logic. The reading materials, exercises, and classroom discussion have not met the learning goals of this course. Therefore, an additional media needs to be implemented to improve the learning process. The program of macro recording in Microsoft Office can facilitate the students to have exercises and material analysis autonomously beyond the classroom activities. This study belongs to action research. The participants were the sixth semester students of Civil Engineering and Planning, Faculty of Engineering, Yogyakarta State University, who joined computer programming course for 4 months. This research employed two cycles, which was started by planning, implementation & observation and finally, reflection. The result of the research showed that there was an improvement of the learning achievement from 2.8 into 3.29 for computer programming course by utilizing macro recording facility of Microsoft product. Keywords: Recording Macro, Learning Process